Equipes diretivas do município de Esteio: gestão democrática e qualidade da educação - Mantay, Carla (Universidade do Vale do Rio do Sinos, 2009)
This work focuses on a form of operationalise the democratic management in the framework of public school organizations of basic education, in a school management not carried out by an individual, but by a collective designated " directive staffing ". This work analyzes the democratic management in conjunction with the quality of education, whereas the " directive staffing " as authors and important actors in educational policy of the city. The theoretical framework identifies the cycles of policies in local and global level and its implications to the practice of such teams. Theoretical work recovers legal texts on the concepts of staffing directors, democratic management and quality and discusses the policies under views inter-related: retaking how were produced and applied the rules governing the action of teams guidelines and the ways the teams understand, incorporate and process them. Therefore, various contexts of policies and as the teams commands arise in these contexts, as actors and authors of its
Keywords: equipes diretivas; qualidade da educação; gestão democrática; directive staffing; quality of the education; democratic management; Ciências Humanas